VOLCANOES AND THEIR HAZARD TO AVIATION - Gordeev E.I.; Girina O.A. (My University, 2014)
In March 2013, the Kamchatkan Volcanic Eruption Response Team (KVERT) celebrated the 20th anniversary of its activity. This team, which was created by the joint efforts of Russian and American scientists, analyzes on a daily basis the data supplied by the complex (seismic, video, visual, and satellite) monitoring system of volcanoes of Kamchatka and the Northern Kuril Islands to notify airline companies and all interested organizations about potential hazards.
Keywords: 38.37.25 Вулканология